EXPLORATORY ANALYSIS OF MID-DAY MEAL SCHEME IN PRIMARY SCHOOLS OF LUCKNOW, UTTAR PRADESH - Choudhary , Rekha; Chandra, Ritu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper provides an exploratory analysis of the Mid-Day Meal Scheme (MDMS) in primary schools of Lucknow, Uttar Pradesh using secondary data. It examines the scheme’s objectives, recent developments, public-private partnerships, and its impact on children’s nutritional well-being and educational outcomes. By focusing on the unique challenges and successes within Lucknow, this paper aims to contribute to a better understanding of how MDMS operates at the local level and suggest pathways to enhance its effectiveness.